A concise Nuxalk-English dictionary - Nater, H. F. (Book collections on Project MUSE., 1990)
This dictionary lists in alphabetical order over 2000 Nuxalk morphemes, as well as sample words and sentences, gathered by the author at Bella Coola, British Columbia between 1972 and 1983.